Metodologias para validação de proteções de linhas de transmissão - Eduardo Martins Gonçalves (2012)
This work has the objective to describe the current application of protection and control equipments in transmission system and to present the resources, methodologies and procedures that are used by protection specialists on accomplishment of tests in transmission line protection systems and other interlinked ones, endowed with teleprotection schemes, during the process of commissioning of new facilities and other maintenance processes. Due to their characteristics,the presented methodologies constitute nowadays, the main alternative in order to complete validate the operational performance of the protection systems, schemes and equipments of associated eleprotection, breakers, automatic reclosure schemes with synchronism check and eventual special schemes of protection that depend on the exchange of information among the involved terminals. It will be also presented a methodology for validation of equipments and protection and control schemes, using real time digital simulation, in order to adapt to the new reality imposed by the digital technology and due to the increase electric power system complexity.